ETHNOBOTANY OF WILD AND MEDICINAL PLANTS OF THE TASHKENT REGION - Farangiz Alimova (Modern American Journals, 2025)
This article examines the ethnobotany of wild medicinal plants distributed in the territory of Tashkent region, which are used in traditional medicine. The introduction emphasizes the relevance of studying and conserving these plants, as they hold great importance for the pharmaceutical industry and the region’s biological resources. The research methods included field surveys, taxonomic analysis, and the collection of information on the use of plants in traditional medicine through interviews with local residents and the review of literary sources. As a result, the main species of wild medicinal plants, their biological characteristics, and their areas of application in the traditional medicine of the Tashkent region were identified. The discussion highlights the importance of monitoring and sustainable use of these plants, as well as recommendations for their conservation and integration into modern pharmacy. The obtained results contribute to expanding scientific knowledge in the field of ethnobotany and the preservation of the region’s plant biodiversity.
Keywords: Medicinal plants, wild plants, ethnobotany, taxonomic analysis, field research, traditional medicine, flora of Tashkent region, biological diversity, sustainable use, resource assessment, phytotherapy, pharmacognosy, plant conservation.